2008
DOI: 10.1186/1471-2202-9-s2-s12
|View full text |Cite
|
Sign up to set email alerts
|

The p38α mitogen-activated protein kinase as a central nervous system drug discovery target

Abstract: Protein kinases are critical modulators of a variety of cellular signal transduction pathways, and abnormal phosphorylation events can be a cause or contributor to disease progression in a variety of disorders. This has led to the emergence of protein kinases as an important new class of drug targets for small molecule therapeutics. A serine/threonine protein kinase, p38α mitogen-activated protein kinase (MAPK), is an established therapeutic target for peripheral inflammatory disorders because of its critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 67 publications
(78 reference statements)
0
22
0
Order By: Relevance
“…3A). Similarly, p38α and p38β, human orthologs of Accp38b, were abundantly expressed in brain tissues, and p38α plays an important role in the central nervous system (20,21). Additionally, the expression analysis revealed that Accp38b was responsive to light (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…3A). Similarly, p38α and p38β, human orthologs of Accp38b, were abundantly expressed in brain tissues, and p38α plays an important role in the central nervous system (20,21). Additionally, the expression analysis revealed that Accp38b was responsive to light (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Insights into the mechanisms by which p38α MAPK contributes to proinflammatory cytokine overproduction in the CNS suggest that this kinase could also be a valid target for neurological disorders (reviewed in REF. 3). For example, the p38 MAPK pathway is activated in neurons and glia in the brains of patients with early-stage Alzheimer’s disease and in rodent models of neurodegenerative disease, as assessed by staining for phosphorylated (activated) p38 MAPK.…”
Section: Examples Of Cns Protein Kinase Targetsmentioning
confidence: 99%
“…Half of the oncology pipeline are kinase inhibitors, but none of the disclosed CNS candidates seems to target protein kinases. Nevertheless, there is increasing interest in the development of kinase-targeted therapeutics for CNS indications3-11, and the established success in other disease indications provides encouragement for the development of small-molecule kinase modulators for CNS disorders.…”
mentioning
confidence: 99%
“…Taken together, our results showing the inhibition of mast cell degranulation by PGD 2 through the DP1 receptor may potentially be attributed to the activation of adenyl cyclase by the G s protein, leading to the increased production of cAMP. The p38 MAPK is known to have a role in proinflammatory cytokine production in response to various external stimuli (Saklatvala, 2004;Borders et al, 2008). We have also shown that activation of this kinase by STZ in keratinocytes can lead to nonclassical anti-inflammatory effects by the production of PGE 2 (Sur et al, 2008a).…”
Section: Discussionmentioning
confidence: 93%